Entrepreneurship in the global economy : engine for economic growth - Kressel, Henry; Lento, Thomas V. (Cambridge University Press, 2012)
"Entrepreneurs have long been drivers of innovation in developed countries. They start companies and create new industries that keep economies strong and prosperous. Today, however, in developing nations such as China, state-controlled economies are building robust industries at stunning speed and siphoning off jobs from the West. How can entrepreneurs function in the face of this challenge? Can they continue to create economic value in a globalized business environment? This book addresses the crucial issue of state planning vs. free enterprise and examines specific problems surrounding entrepreneurship in the global economy through nine case histories of entrepreneurial companies. It also looks at how and why government gets involved in economic growth and how entrepreneurs contribute to economic value. Based on this analysis, the authors argue that companies can succeed, even in controlled economies, by understanding the customs and policies of countries where they do business"-- Provided by publisher